2018
DOI: 10.1007/s00417-017-3897-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiplatelet and anticoagulant agents in vitreoretinal surgery: a prospective multicenter study involving 804 patients

Abstract: This study showed that AP and AC agents were not a factor associated with hemorrhagic complications during vitreoretinal surgery. The continuation of these treatments should be considered without risk of severe hemorrhagic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
1
8
0
2
Order By: Relevance
“…We thank our colleague Andrei Grzybowski for his interest in our paper, recently published in Graefe's Archives for Clinical and Experimental Ophthalmology [1]. We agree with him that continuing or discontinuing antithrombotic drugs before any ocular surgery is still a matter of debate and may differ in diverse countries and cultures [2].…”
mentioning
confidence: 66%
“…We thank our colleague Andrei Grzybowski for his interest in our paper, recently published in Graefe's Archives for Clinical and Experimental Ophthalmology [1]. We agree with him that continuing or discontinuing antithrombotic drugs before any ocular surgery is still a matter of debate and may differ in diverse countries and cultures [2].…”
mentioning
confidence: 66%
“…We thank Dr. Zarei for his comments about our paper about antiplatelet and anticoagulant agents in vitreoretinal surgery [1]. We agree about the fact that the discontinuation of antiplatelet agents should be discussed with the patients and his/ her cardiologist before surgery with full informed consent.…”
Section: Dear Editormentioning
confidence: 86%
“…Some investigators have also suggested that anticoagulant therapy interruption could produce a rebound hypercoagulability state due to the alteration of the balance between vitamin K dependent factors and proteins C and S (16)(17)(18)(19). Moreover, it is a situation that makes it necessary to postpone surgery Even though some authors have found an increased risk of haemorrhagic complications in anticoagulated patients undergoing PPV, the incidence has been low, without statistical significance and without serious consequences for visual acuity (9,10,11,20,21). Dayani In contrast to other eye surgeries, vitreoretinal surgery has been considered to pose a high haemorrhagic risk (22).…”
Section: Discussionmentioning
confidence: 99%
“…So far, no trial has compared the perioperative complications and visual results associated with continuation or interruption of oral anticoagulant therapy before PPV under retrobulbar anaesthesia in a prospective and randomized manner. There is only one study that has evaluated this issue in a prospective but non-randomized manner, but the authors included a small number of patients, did not standardise the management of anticoagulant agents in the perioperative period and did not record all haemorrhagic complications (11). Moreover, there is only one study that has evaluated haemorrhagic intraoperative complications associated with PPV in patients under treatment with novel anticoagulant therapy (10).…”
mentioning
confidence: 99%